Effect of Lowering the Dose of Varenicline on Alcohol Self-administration in Drinkers With Alcohol Use Disorders. Issue 3 (May 2016) - Verplaetse, Terril L.; Pittman, Brian P.; Shi, Julia M.; Tetrault, Jeanette M.; Coppola, Sabrina; McKee, Sherry A.
Abstract : Objectives: Varenicline (2 mg/d) has been shown to be efficacious in reducing alcohol consumption. A lower dose of varenicline may be effective in reducing alcohol use while minimizing the potential for side effects. Methods: This double-blind, placebo-controlled investigation examined the effect of varenicline (0, 1, 2 mg/d) on alcohol consumption in nontreatment-seeking adults meeting the Diagnostic and Statistical Manual of Mental Disorders 4th Edition (DSM-IV) criteria for alcohol use disorders (N = 60). Following 7 days of medication pretreatment, participants were administered a low fixed dose of alcohol (0.3 g/dL), and subjective and physiologic responses were assessed. A 2-hour ad libitum alcohol self-administration period followed. We also explored relationships between plasma varenicline levels and consumption. Results: Overall, frequency and severity of adverse events were minimal. The 1 mg/d dose reduced the frequency of insomnia compared with the 2 mg/d dose. The 2 mg/d varenicline dose versus placebo reduced alcohol craving and showed limited effect on reduced alcohol consumption. Alcohol craving and consumption did not differ between the 1 mg/d varenicline dose versus placebo. Trough varenicline plasma levels greater than or equal to 3 ng/mL were associated with reduced drinking and levels greater than or equal to 5 ng/mL were associated with reduced heavy drinking. Conclusions: Overall, we found no evidence supporting an effect of 1 mg/d varenicline on craving or consumption, suggesting that doses of varenicline less than 2 mg/d may not be effective in reducing alcohol-related outcomes. Importantly, results suggest that higher plasma levels of varenicline may be needed to maximize the effect of varenicline on alcohol consumption and should be investigated in drinkers meeting criteria for alcohol use disorders.